Psikoloji Perspektifinden Ferîdüddîn Attâr 'ın Yedi Vadisi ve Nefis Mertebelerinin İncelenmesi - (:unkn) unknown (My University, 2016)
Bu makalede Attâr'ın eserlerinde metaforik olarak anlattığı Hakk'ı arayış ve varoluşsal yolculuk tasavvuf anlayışı ve günümüz psikoloji perspektifi harmanlanarak incelenmiştir. Bu incelemede Attâr'ın hikâyelerindeki tasavvuf görüşleri ile insanın karakter özellikleri, yaşam tarzı, bilişsel yapısı, varoluşsal yolculuğu ve kendini gerçekleştirme süreci ilişkilendirilmiş ve yorumlanmaya çalışılmıştır. Yorumlama yapılırken Mantık Al-Tayr eserinde yer alan "istek, aşk, marifet, istiğna, tevhit, hayret ve fakr-u fena" isimli vadiler ve bu vadilerden geçiş için gerekli olan özellikler ile nefis mertebeleri temel olarak alınmıştır. Ayrıca yorumlama yapılırken Attâr'ın "İlâhiname, Esrarname " eserlerinden de faydalanılmıştır.

This article examines the search for Truth and the journey of existence as explained metaphorically in the works of Farid ud-Din Attar by blending Sufi understanding and a contemporary psychological perspective. It attempts to associate and review people's characteristics, life styles, cognitive structures, existential journeys, and processes of self-realization through the Sufi views in Attar's stories. The Valleys of Quest, Love, Understanding, Independence and Detachment, Unity, Astonishment and Bewilderment, and Deprivation and Death that occur in Mantiq al-Tayr (The Conference of the Birds) are basically accepted through interpretation as the stages of human desires along with the characteristics that are required to transition from these valleys. This research also benefitted by interpreting other works by Attar, the IlahiNama (Book of God) and Asrar-Nama (Book of Mysteries).
Attar of Nishapur's Seven Valleys and the Stages of Human Cravings from a Psychological Perspective
Keywords: Psikoloji